A Better Future for All Nigerians : Nigeria Poverty Assessment 2022 - World Bank (Washington, DC, 2022)
This poverty assessment lays out the broad development challenges that Nigeria faces, which constrain the country’s poverty reduction. The discussion provides the backdrop for the detailed analysis presented in later parts of the report. First, the introductory section links Nigeria’s macroeconomic performance with its prospects for poverty reduction, emphasizing that the country may be struggling to stimulate inclusive growth: that is, growth that would benefit Nigerians across the welfare distribution. Second, the section examines the proliferating climate and conflict shocks that Nigeria faces, which further complicate poverty reduction. Third, the section describes how the “double shock” of COVID-19 has affected Nigeria, through both health and economic impacts and discusses the recent acceleration in inflation. Finally, this introduction considers Nigeria’s data landscape, explaining how new microdata offer vital insights into the country’s pathways out of poverty.